2016
DOI: 10.5137/1019-5149.jtn.19450-16.0
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve in anatomo-electrophysiological correlations in subthalamic nucleus stimulation

Abstract: Parkinson's disease and other movement disorders, but not limited to them (4,13). The anatomical target definition based on neuroradiological investigation can be supported by intraoperative microrecording using simultaneously or sequentially implanted intracerebral microelectrodes and intraoperative MATERIAL and METHODS:The trajectories of right (first implanted) and left electrodes were compared in the first 50 patients operated on (Group 1) and the next 50 patients (Group 2). RESULTS:In Group 1, 52% of cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Thus, there was no evidence that greater surgical experience would have made a difference. Although our dataset included the commencement of a new DBS service, both members of the surgical team had substantial prior experience in DBS and were operating a high-volume service, factors which may improve surgical outcomes [29][30][31]. We also found no difference in location error between electrodes that were placed with (21.2%) or without a preceding microelectrode trajectory change.…”
Section: Plos Onementioning
confidence: 77%
See 1 more Smart Citation
“…Thus, there was no evidence that greater surgical experience would have made a difference. Although our dataset included the commencement of a new DBS service, both members of the surgical team had substantial prior experience in DBS and were operating a high-volume service, factors which may improve surgical outcomes [29][30][31]. We also found no difference in location error between electrodes that were placed with (21.2%) or without a preceding microelectrode trajectory change.…”
Section: Plos Onementioning
confidence: 77%
“…For example, previous studies of mixed DBS targets have suggested that the first hemisphere implanted may have a smaller error, suggesting that clinicians should implant the most clinically important side first [26,27]. Surgical experience is considered an important determinant of DBS outcomes and clinicians are encouraged to accrue an adequate caseload under supervision before embarking on their own DBS practice [28][29][30][31]. The exact surgical method to implant STN DBS is also controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The results confirmed a higher percentage of central electrodes on the first side implanted in patients 1-50 (right 52%, left 38%). The percentages of central electrodes in patients 51-100 substantially increased on the right (76%) and left sides (78%), thereby confirming the learning curve effect (32). However, this learning curve effect in GPi patients has not been confirmed.…”
Section: Learning Curvementioning
confidence: 83%
“…Clinical experience [ 5 , 6 , 7 ] shows that the position of the DBS contact finally activated for chronic stimulation to induce the best clinical outcome often differs from the intraoperatively chosen position. Possible reasons may include brain shift or the subjective interpretation of stimulation test results.…”
Section: Introductionmentioning
confidence: 99%